Rehabilitation of the knee following sports injury - de Carlo, M.; Armstrong, B. (Clinics in Sports Medicine, 2010)
Rehabilitation of a knee injury is done in a criterion-based progression that is based on individual progress from one phase to another and not on a prespecified period of time. If the rehabilitation deviates from this approach, the body will react with adverse affects such as inflammation, pain, and further injury. Delay in the entire rehabilitation program will delay the athlete in meeting goals and returning to play. Phase I focuses on restoration of range of motion, pain modulation, inflammatory control, modification of activities, and gait training. Phase II is characterized by gaining full range of motion, demonstration of normal gait pattern, basic to advanced strengthening and flexibility, appropriate cardiovascular conditioning, and proprioception retraining. Phase III allows functional return to prior activity level. This phase includes a sport/occupational-specific functional progression. Utilizing a trained rehabilitation specialist will allow the athlete/individual an effective and efficient return to prior level of function.